2019
DOI: 10.1016/j.agee.2018.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal fungi in wood-pastures: Communities are determined by trees and soil properties, not by grazing

Abstract: Traditional rural biotopes such as wood-pastures are species-rich environments that have been created by low-intensity agriculture. Their amount has decreased dramatically during the 20th century in whole Europe due to the intensification of agriculture. Wood-pastures host some fungal species that prefer warm areas and are adapted to semi-open conditions, but still very little is known about fungi in these habitats. We studied how management, historical land-use intensity, present grazing intensity, time since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 39 publications
6
12
0
Order By: Relevance
“…Because of the reduced plant biomass, soil temperature and light increases and this seems to improve the fruiting conditions for many fungal species (Nitare and Sunhede, 1993;Olff and Ritchie, 1998;Pykälä, 2001). However, in our previous study (Tervonen et al, 2019), we found that ectomycorrhizal fungal species did not have higher species richness on grazed wood-pastures than on abandoned ones. Also, Juutilainen et al (2016) found that wood-pastures have lower wood-inhabiting fungal species richness than natural forests.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…Because of the reduced plant biomass, soil temperature and light increases and this seems to improve the fruiting conditions for many fungal species (Nitare and Sunhede, 1993;Olff and Ritchie, 1998;Pykälä, 2001). However, in our previous study (Tervonen et al, 2019), we found that ectomycorrhizal fungal species did not have higher species richness on grazed wood-pastures than on abandoned ones. Also, Juutilainen et al (2016) found that wood-pastures have lower wood-inhabiting fungal species richness than natural forests.…”
Section: Introductionmentioning
confidence: 54%
“…In addition, Rousk et al (2009) found that fungal species richness peaked at pH 4.5 on arable managed land. In our previous study with ectomycorrhizal fungi, species richness decreased with soil moisture in abandoned wood-pastures, whereas soil pH did not have a significant effect on species richness (Tervonen et al, 2019).…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Soil fungi are a key component of below-ground biological communities and play an important role in decomposition and nutrient recycling through a number of microbiological and ecological processes (Setala and McLean, 2004;Berg and McClaugherty, 2008;Smith and Read, 2010;Voříšková and Baldrian, 2013;Gaggini et al, 2018). Soil fungi have a widespread ecological distribution and the diversity of the fungal community can be affected by many variables such as precipitation, temperature, root exudates, available nutrients, plant community composition, and cropping pattern (Newsham et al, 2016;Nagati et al, 2018;Zhang et al, 2018;Schmidt et al, 2019;Tervonen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%